THE RESEARCH PROCESS IN THE SOCIAL SCIENCES - Smilgienė, Silvija (Verbum, 2015)
THOMAS, Gary 2010. How to do Your Research Project. A Guide for Students in Education and Applied Social Sciences. London: SAGE Publications. 254 p. ISBN 978-1-84787-442-9